Impact of teacher leadership on school effectiveness as perceived by teachers and school principals: a logistic regression study - Sajid, P. K. Muhammed (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study was to determine the relationship between aspects of teacher leadership and school effectiveness on the basis of perception of teachers and principals. It focused on seven aspects of teacher leadership derived from literature, while trying to investigate (a) the perceptions of teachers and principals on the impact of teacher leadership on the school effectiveness, (b) the predictors of the teacher leadership, (c) the dimensions of the teacher leadership that predict school effectiveness, and (d) the differences of perceptions of male and female teachers on seven aspects of the teacher leadership. The study used logistic regression analysis to study these seven aspects. A survey questionnaire developed by the researcher and aimed to measure the perceptions of principals and teachers of the impact of teacher leadership on school effectiveness was given to 34 principals and 200 teachers of the schools affiliated to Majlisu Tha'alimi al-Islami, Kerala, India. Besides, the Teacher Leadership School Survey developed by Katzenmeyer and Katzenmeyer and meant to identify the predictors of the teacher leadership and to evaluate how male and female teachers vary in their perceptions of the seven aspects of the teacher leadership was distributed only among the teachers. Descriptive statistical analysis, simple linear regression analysis, binary logistic regression analysis, and independent sample T-test were employed in this study to analyse the data. Findings revealed that the majority of the participants of both group -principals (100%) and teachers (97.1%) - were confident enough in connecting school effectiveness with teacher leadership. Although the views of teachers and principals seemed slightly varied on involvement of the teachers in various leadership roles in the school, a large number of them believed that teachers' participation in decision making process and in different leadership responsibilities has very positive impact on school effectiveness. Further, the study found that out of four demographic variables, i.e., age, gender, education level, and experience of the participants, only gender was the predictor of teacher leadership. The positive effect of gender on teacher leadership is statistically significant at the 0.05 level. Moreover, of the seven aspects of teacher leadership, the study found that only Developmental Focus, Participation and Open Communication were the predictors of school effectiveness. Finally, the study discovered that the female teachers were significantly different from male teacher in their views on four of the seven aspects of teacher leadership. These were developmental focus, recognition, collegiality and open communication.